The Effect of Color Saturation on Brand Attitudes in Brand Logo Redesign - Hisashi Kawamata; Takeshi Moriguchi (Maketingu Janaru, 2023)
An increasing number of brands have been redesigning their logo. While the manner of change varies, some brands only change the logo color. This study examined the effect of changes in color saturation during brand logo changes on consumers’ brand attitudes. It is known that saturation, which indicates the vividness of a color, gives consumers an impression of energy and dynamism. Therefore, we examined the impact of changes in brand logo color saturation on brand attitudes by enhancing perceptions of brand energy. Throughout three experiments, it was found that 1) a highly saturated logo enhances consumers’ perception of brand energy; 2) increasing saturation when changing the logo color increases brand energy perception, which in turn increases attitude toward the brand; and 3) the effect of brand energy perception on attitude toward the brand is stronger for global brands than for domestic brands. This study, which clarified the relationship between the influence of saturation on brand attitude when changing a brand logo, may provide many suggestions for brands considering logo redesign.